Thermal stability of Lithium-ion batteries: Case study of NMC811 and LFP cathode materials. (2022) - El Moutchou, S.; Aziam, H.; Mansori, M.; Saadoune, I.
Abstract: The rising need for safe and cost-efficient energy storage systems has urged researchers to deploy more efforts into finding solutions for the thermal runaway issue especially in layered lithium metal oxide cathodes. In this work, the thermal stability of two kinds of prepared cathodes, layered oxide LiNi0.8 M0.1 Co0.1 O2 (NMC811) and phospho-olivine LiFePO4 (LFP), was studied and compared to the commercial ones. To this end, the thermal behavior of the electrodes at 100% state-of-charge was investigated using differential scanning calorimetry (DSC). The obtained results showed that LFP cathodes are thermally stable compared of NMC811.